SISTEM PENDUKUNG KEPUTUSAN MODEL PENENTUAN SISWA TELADAN PADA SMK BONAVITA DENGAN PENDEKATAN LOGIKA FUZZY - Dedy Iskandar; Taviv Prahasta; Ardi Rahmadani (UNIVERSITAS RAHARJA, 2018)
School is an institution that not only teach science or study but also is very important to educate the students. The education will influence or change the behavior, character, personality, way of thinking, maturity and etc, because the education is expected the student not only understand or master of science and technology but also have good character and personal. National education goals also called general purpose is education goals to be achieved at the national level. Indonesia’s national education goals listed in law Republic Indonesia number 2 1989, about the national education system chapter 2 verse 4 said: national education the nation and develop human whose faith and fear of God, good character, knowledge and skills, physical and spiritual health, personality and independence and sense responsibility for society and nationality. To achieve national education goals, vision and mission of the school, the scholl students need to choose someone who can be role model for other students in learning, behavior, attitudes and how to interact in school or outside the school cenvironment. The head master and the teacher make the criteria or requirements to determine who will be role model and they use an approach that can be done by using Fuzzy logic . And the assesment’s criteria can be done by looking at the attitude, discipline, the average of mark, the organization, and involved in drugs. That approached is expected to choose a role model of student effectively. From that criteria they make a decision support system to determine thet role mode student.